2020
DOI: 10.1002/advs.202001996
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Control of Ultrafast Spin Current to Induce Single Femtosecond Pulse Switching of a Ferromagnet

Abstract: New methods to induce magnetization switching in a thin ferromagnetic material using femtosecond laser pulses without the assistance of an applied external magnetic field have recently attracted a lot of interest. It has been shown that by optically triggering the reversal of the magnetization in a GdFeCo layer, the magnetization of a nearby ferromagnetic thin film can also be reversed via spin currents originating in the GdFeCo layer. Here, using a similar structure, it is shown that the magnetization reversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…In this experiment, the composition of Gd used was 33%, where a single GFC layer cannot exhibit single-shot AOS. 70) The MOKE hysteresis loop for the Gd-rich GFC= Cu=CoPt spin-valve is shown in Fig. 8 images after irradiation with fs laser pulses are shown in Fig.…”
Section: Single-shot Aos Using Spin-valvesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, the composition of Gd used was 33%, where a single GFC layer cannot exhibit single-shot AOS. 70) The MOKE hysteresis loop for the Gd-rich GFC= Cu=CoPt spin-valve is shown in Fig. 8 images after irradiation with fs laser pulses are shown in Fig.…”
Section: Single-shot Aos Using Spin-valvesmentioning
confidence: 99%
“…69) Furthermore, our recent results demonstrated that energyefficient single-shot AOS of FMs can be obtained by increasing the amount of spin-current using a FM=nonmagnetic metal=GFC spin-valve structure. 70) From the experiments and calculations pertaining to the ordering temperature of the FMs in a spin-valve, the mechanism of single-shot AOS of the FMs can be qualitatively explained by the combined effects of ultrafast quenching of magnetization and the transfer of angular momentum from Gd. 71) In this review, we first describe the AOS in ferrimagnetic GFC and the mechanism behind single-shot AOS.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] AO-HIS has also been recently observed in TbCo. [4] Nowadays, GdFeCo is used to perform the AO-HIS of Co/Pt [5][6][7] or CoNi/Pt [8] ferromagnetic multilayers. Moreover, it is possible to tune the Dzyaloshinskii-Moriya interaction in thin GdFeCo ferrimagnetic alloys, [9] a relevant property for skyrmions formation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in noncollinear magnetic systems THz standing spin waves are excited by the spin-transfer torque [5,6]. Moreover, the spin currents can play an assisting role in deterministic all-optical switching [7][8][9][10][11]. In other words, optically induced spin currents provide a versatile tool to manipulate magnetic systems on ultrashort timescales and pave the way towards future spintronic technologies.…”
Section: Introductionmentioning
confidence: 99%